Reintroduction biology : integrating science and management - John G. Ewen, ;Armstrong, Doug P.;Parker, Kevin A.;Seddon, Philip J. ([Place of publication not identifed] : [publisher not identified], 2012)
This book in turn evolved from the 2008 symposium, but it is definitely not a conference proceedings.
Animal translocations : what are they and why do we do them? -- A tale of two islands : the rescue and recovery of endemic birds in New Zealand and Mauritius -- Selecting suitable habitats for reintroductions : variation, change and the role of species distributions modelling -- The theory and practice of catching, holding, moving and releasing animals -- Dispersal and habitat selection : behavioural and spatial constraints for animal translocations -- Modelling reintroduced populations : the state of the art and future directions -- Monitoring for reintroductions -- Adaptive management of reintroduction -- Empirical consideration of parasites and health in reintroduction -- Methods of disease risk analysis for reintroduction programmes -- The Genetics of reintroductions : inbreeding and genetic drift -- Genetic consequences of reintroductions and insights form populations history -- Managing genetic issues in reintroduction biology -- Summary
Includes bibliographical references and index.
Keywords: BIOLOGY